Developing Website-Based Gamification Learning Media on Debate Texts in Indonesian Language Learning - Diana, Purwati Zisca; Indriyani, Ika Putri; Sulistiyono, Roni; Wulandari, Putri Ayu; Prafitra, Revola Aridya (Universitas Pendidikan Mandalika, 2024)
This research and development is motivated by the lack of creative learning media in Indonesian language learning, especially in grade X high school debate text material. Therefore, there is a need to develop website-based gamification learning media that makes learning more creative and innovative. Until the researcher developed the Website-Based